Diagnostic and Prognostic Value of Monocyte-to-Lymphocyte Ratio and Red Cell Distribution Width to Lymphocyte Ratio in Primary Biliary Cholangitis - Jiang, Yanting; Wang, Jian; Wu, Huiling; Zhou, Wei; Li, Sihui; Jin, Min (Turkish Journal of Gastroenterology, 2023)
Objective: The aim of this study is to assess levels of monocyte-to-lymphocyte ratio and red cell distribution width-to-lymphocyte ratio in primary biliary cholangitis patients and excavate their clinical significance.Methods: The levels of monocyte-to-lymphocyte ratio and red cell distribution width-to-lymphocyte ratio in the primary biliary cholangitis, autoimmune hepatitis, and healthy controls were compared, and correlations between monocyte-to-lymphocyte ratio, red cell distribution width-to-lymphocyte ratio, and Mayo score were analyzed. The area under the receiver operating characteristic curve was utilized to analyze the diagnostic value of monocyte-to-lymphocyte ratio and red cell distribution width-to-lymphocyte ratio for primary biliary cholangitis.Results: Monocyte-to-lymphocyte ratio and red cell distribution width-to-lymphocyte ratio in primary biliary cholangitis were higher than they were in autoimmune hepatitis and healthy controls (each, P < .05). Area under the s of monocyte-to-lymphocyte ratio and red cell distribution width-to-lymphocyte ratio in diagnosis of primary biliary cholangitis were 0.821 and 0.797, respectively (each, P < .001). The combination of monocyte-to-lymphocyte ratio and red cell distribution width-to-lymphocyte ratio increased the diagnostic value of primary biliary cholangitis (area under the receiver operating characteristic curve = 0.868, P < .001). The correlation analysis showed that monocyte-to-lymphocyte ratio and red cell distribution width-to-lymphocyte ratio were positively correlated with Mayo score (r-MLR = 0.459, r-RLR = 0.522, P < .001 for each). Red cell distribution width-to-lymphocyte ratio was independently associated with Mayo score (P = .036) by multiple linear regression. In primary biliary cholangitis patients with Child–Pugh classification, monocyte-to-lymphocyte ratio and red cell distribution width-to-lymphocyte ratio levels in class B and class C were significantly higher than in class A (each, P < .05).Conclusion: Elevated levels of monocyte-to-lymphocyte ratio and red cell distribution width-to-lymphocyte ratio may prove to be useful markers for estimating the prognosis of primary biliary cholangitis, and the combined detection of monocyte-to-lymphocyte ratio and red cell distribution width-to-lymphocyte ratio has some clinical diagnostic value in patients with primary biliary cholangitis.Cite this article as: Jiang Y, Wang J, Wu H, Zhou W, Li S, Jin M. Diagnostic and prognostic value of monocyte-to-lymphocyte ratio and red cell distribution width to lymphocyte ratio in primary biliary cholangitis. Turk J Gastroenterol. 2023;34(2):170-176.